(untitled) (Journal of National Institute of Neurosciences Bangladesh, 2017)
Background: Infant and young child feeding (IYCF) practices play vital role for the growth & development in the early months of life. Objective: The purpose of the present study was to determine and to identify the patterns and influencing factors of feeding practices in infant and young children of 0-2 years old in Bangladesh. Methodology: A descriptive type of cross sectional study was carried out to assess the pattern of infant & young child feeding practices by the rural mothers of Bangladesh with a sample size of 450 during the months of January to December of 2015. Result: Out of 450 children, 51.1% are female & 48.9% are male. The proportions of infants with early initiation of breastfeeding (13.6%) and exclusive breastfeeding fewer than six months (57.3%) and infants who received complementary feeding at the age of 68 months (55.7%) were low. It showed that 90.4% of mothers have knowledge on exclusive breast feeding but only 57.3% of them have practiced it for 4-6 months. It further revealed that only 8.4% of mothers & 13.6 % of fathers were illiterate. The main problems revealed from the study were late initiation of breastfeeding, low rates of exclusive breastfeeding, and inappropriate complementary feeding practices. It further revealed that 69.3% of the respondents had two or less children and 30.7% had three or more children. Conclusion: Majority of the respondents have the knowledge on complementary feeding, knowledge on preparation of complementary feeding, knowledge on preparation of food by grains, knowledge on preparation of food by milk and milk products and knowledge on preparation of food by meat, fish, poultry, liver. Journal of National Institute of Neurosciences Bangladesh, 2016;2(1):19-25